Carbapenem-resistant Acinetobacter baumannii infections among diabetic and non-diabetic patients and possible effective combination treatments - Aya M. Ghareeb; Marwa M. Raafat; Naglaa S. Bazan; Reham Samir (SpringerOpen, 2024)
Abstract Background Carbapenems are one of the most noteworthy choices for treating multidrug-resistant Acinetobacter baumannii (A. baumannii). Currently, carbapenem-resistant A. baumannii (CRAB) represents a healthcare problem worldwide, particularly among diabetic patients who are more susceptible to microbial infections. The aim of this study was to investigate the differences in antibiotic susceptibility profiles, the abundance of carbapenem resistance genes across A. baumannii-infected diabetic and non-diabetic patients, and the antimicrobial activity of different antibiotic combinations on highly resistant isolates. Methods Data of 99 A. baumannii-infected patients were collected during the period from 2018 to 2022 and categorized according to patients' diabetes status into either diabetic or non-diabetic group. A total of 45 A. baumannii isolates were collected during 2021 and 2022 from the main hospital laboratory to be reidentified and genetically confirmed. Antibiotic susceptibility, including carbapenems, was determined using disc agar diffusion and broth microdilution methods. The isolates were screened for OXA-23, GES, VIM, and NDM carbapenem-resistant genes. Five antibiotic combinations were assessed using the double-disk synergy and checkerboard methods. Results The findings of the current study revealed that multidrug resistance increased gradually, from 56% in 2018 to 95.6% in 2022. Moreover, CRAB increased among diabetics and non-diabetics. Resistance rates of imipenem, meropenem, and doripenem reached 68.8%, 61.8%, and 47.4% in diabetics and 97.9%, 83.3%, and 50% in non-diabetics, respectively. The VIM gene was the most prevalent gene with prevalence rates of 100% and 96.15% in diabetics and non-diabetics, respectively. Moreover, all A. baumannii isolates carried at least two of the selected carbapenem-resistant genes. Across the different used combinations, only the tigecycline-meropenem combination showed synergistic activity in 50% of diabetic and 66.7% of non-diabetic isolates. Conclusions An increased carbapenem resistance was observed among A. baumannii-infected individuals, both diabetic and non-diabetic. The MEM/TCG combination was the only one that showed synergistic or additive effects against highly resistant isolates making it a viable alternative treatment option.